2021
DOI: 10.7759/cureus.12861
|View full text |Cite
|
Sign up to set email alerts
|

Arrhythmias in Neonates and Infants at a Tertiary Care Center

Abstract: Background Limited data about arrhythmias in neonates and infants are coming out from the Middle East. Objectives To evaluate different types of arrhythmias in neonates and infants at the American University of Beirut Medical Center (AUBMC), a tertiary care center in Lebanon, with the focus on the nature of arrhythmia, treatment modalities and relation to surgery. Methods Data were collected retrospectively from the hospital records. We included all neonat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…As in our investigation, Marwan Refaat et al [12] conducted a study of arrhythmia in neonates and babies in a tertiary care institution in Lebanon. They found that 91.1% of the study patients had different forms of tachyarrhythmias and only 8.89% out of their patients had Bradyarrhythmias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As in our investigation, Marwan Refaat et al [12] conducted a study of arrhythmia in neonates and babies in a tertiary care institution in Lebanon. They found that 91.1% of the study patients had different forms of tachyarrhythmias and only 8.89% out of their patients had Bradyarrhythmias.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study AV block was the more common pediatric bradycardia (47 patients with AV nodal disease Vs 8 patients with sinus node disease). Also, Marwan Refaat et al [12] found AV blocks to be a more common bradycardia than sinus node dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Since data related to JET occurring in neonates and infants are scarce from the Middle East, we analyzed all recorded cases of JET in this age category at a tertiary care center in Lebanon hospitalized between January 1, 2013, and December 31, 2017, as a part of a study on arrhythmias in neonates and infants done over the same time frame. 8,9 We aim to highlight the epidemiology, incidence, and management of this rare form of arrhythmia in this age group.…”
Section: Introductionmentioning
confidence: 99%